Dengue-2 Vaccine: Viremia and Immune Responses in Rhesus Monkeys - Scott, Robert McN. (1980)
Studies were undertaken in Indian rhesus monkeys (Macaca mulatta) to determine the safety, potency, immunogenicity, and mosquito infectivity of a small-plaque, temperature-sensitive variant of dengue type 2 (DEN-2) virus, a vaccine candidate. Fifteen monkeys were inoculated subcutaneously with the vaccine virus, ten receiving 10(3.1) plaque-forming units (PFU) and five receiving 10(4.5) PFU. After primary immunization, viremia was detected in only one monkey, a recipient of the higher dose of vaccine. The recovered virus had the same growth characteristics as the vaccine strain. Aedes aegypti mosquitoes did not become infected when they were allowed to feed on monkeys that received the lower dose of vaccine. As expected, the immunization produced no evidence of illness in any of the animals. A dose response to vaccine was detected; all five of the high-dose recipients developed neutralizing antibodies, whereas only five of ten low-dose recipients did so. In both groups, neutralizing antibody was often transient. Its presence at 30 days did not always correlate with protection from viremia in those animals challenged 4 to 6 months after vaccination with wild-type DEN-2 virus. However, immunized animals developed anamnestic antibody responses after challenge, and none demonstrated adverse effects to infection. Reimmunization of monkeys 4 months after primary immunization led to the production of low-titered but persistent neutralizing antibody which protected the animals from a wild-type virus challenge.